2023
DOI: 10.21608/bmfj.2023.171855.1699
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prelacrimal Recess Approach Assisted Middle Meatal Antrostomy in Primary Antrochoanal Polyp

Abstract: Background:Primary antrochoanal polyp management is commonly done via middle meatal antrostomy which has a significant risk of recurrence. The prelacrimal recess approach is reported to minimize this risk. Aim: This study aims to compare the results of prelacrimal recess approach assisted middle meatal antrostomy with middle meatal antrostomy alone in the management of primary antrochoanal polyp. Patients and methods: A randomized prospective Comparative Study was performed on sixty patients with primary antro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Further studies will be needed to investigate the potential use of that scoring system in the evaluation of the outcome of the prelacrimal approach. A recent study found a statistically significant difference in postoperative crustations between two groups treated with standard endoscopic sinus surgery (ESS) and the prelacrimal approach (PLA) when comparing their 1-, 3-, and 6-month postoperative follow-up periods [22].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be needed to investigate the potential use of that scoring system in the evaluation of the outcome of the prelacrimal approach. A recent study found a statistically significant difference in postoperative crustations between two groups treated with standard endoscopic sinus surgery (ESS) and the prelacrimal approach (PLA) when comparing their 1-, 3-, and 6-month postoperative follow-up periods [22].…”
Section: Discussionmentioning
confidence: 99%